Indoor propagation prediction and measurements within multistory building for wireless LAN applications - Omer, Abdusamea I. A. (2007)
In recent years, the possibility of using radio for data and voice communications inside the buildings has become an attractive proposition. A prerequisite to the design of indoor radio communication systems is knowledge of indoor propagation characteristics. These characteristics can be used to determine the optimum location of the base station antenna for a desired coverage within a building. Propagation prediction within buildings is made difficult by the occurrence of various propagation phenomena which depend on specific building structures. In this project the investigation for WLAN system is done for three different buildings inside University of Technology Malaysia. The Site Ware Technology's site specific propagation prediction tool is a three-dimensional (3-D) ray tracing code employing modified shoot and bounce ray(SBR) method know as the Vertical Plane Launch (VPL) will be used to predict indoor propagation effects with different building structures to show the prediction of the path loss and the time delay spread for WLAN system inside these buildings, also a comparison between the real time measurements using AirMagnet software and the prediction using VPL software has been done for verification and the AutoCAD tool with the help of Ms Excel, was used to measure all the building's dimensions for highly accurate building database. The results from both prediction and measurement are in form of numbers, so Matlab has been used to present these outputs in 2D display. Finally, based on the evaluation results, we provide a set of recommendations that might help to improve this work and fulfill the indoor user requirements.